RETRACTED ARTICLE: Semantic and prosodic threat processing in trait anxiety: is repetitive thinking influencing responses?. Issue 1 (2nd January 2021) - Busch-Moreno, Simon; Tuomainen, Jyrki; Vinson, David
Abstract : We, the Authors, Editors and Publisher of Cognition and Emotion have retracted the following article: Semantic and Prosodic Threat Processing in Trait Anxiety: Is Repetitive Thinking In fl uencing Responses? By Simon Busch-Moreno, Jyrki Tuomainen & David Vinson, published online: 14 August 2020 https://www.tandfonline.com/doi/full/10.1080/02699931.2020.1804329 Since publication, the Authors discovered two major errors in the statistical analyses. Specifically, (1) the response time data was not standardised before analysis, which resulted in an inflated effect of worry on response time. (2) One of the hyperpriors for the Student t-distribution in the four response time models induced extreme negative values on the distribution's left tail which magnified the artefactual effect. The statistical errors directly impact the validity of the reported results and conclusions. The Authors alerted the issue to the Editor and Publisher and all have agreed to retract the article to ensure the integrity of the scholarly record. We have been informed in our decision-making by our policy on publishing ethics and integrity and the COPE guidelines on retractions. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as 'Retracted'.